Development and regeneration of somatic embryos from leaves-derived calli of Coffea liberica - FITRIA ARDIYANI; Edy Setiti Wida Utami; HERY PURNOBASUKI; SENJA APRILIA PARAMITA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ardiyani F, Utami ESW, Purnobasuki H, Paramita SA. 2020. Development and regeneration of somatic embryos from leaves-derived calli of Coffea liberica. Biodiversitas 21: 5829-5834. Coffea liberica is an important and potentially commercial plant with a high economic value from the Coffea genus. Therefore, the availability of planting material is needed to increase productivity and ensure the sustainability of its farming. Somatic embryogenesis is a powerful propagation method used to produce clonal plants from limited genetic material. In the present research, we have shown that C. liberica could be successfully regenerated in vitro via somatic embryogenesis from leaves derived embryogenic callus. These calli were cultured on Murashige Skoog (MS) medium added with 1 mgL-1 BAP or in combination with 2.4 D (0.5, 1.0, 1.5 and 2 mgL-1) for embryo development induction. Furthermore, the medium containing only BAP was best for embryo development induction after culturing for 12 weeks, with the highest number of cotyledonary stage embryos (17.8%) and producing a total of embryo (20.2). Following cotyledonary stage embryo were cultured on new MS medium containing 0.5 mgL-1 BAP, 0.5 mgL-1 IAA, 0.5 mgL-1 NAA only, and 0.5 mgL-1 BAP in combination with 0.5 mgL-1 IAA or 0.5 mgL-1 NAA. Interestingly, the results showed that cotyledonary stage embryos were converted into complete plants at all treatment, but the MS medium containing 0.5 mgL-1 BAP was found to be the most effective in promoting regeneration with 2.6 leaves per-plantlet and height of 5.2 mm. Based morphological analysis confirm that the development of somatic embryo from leaves-derived calli of Coffea liberica started with the formation of embryo globular, heart, torpedo, cotyledonary stages, and finally conversion of cotyledonary embryo into complete plant.